Analisa Majas Ironi Dalam Narasi Panggilan Yunus 1:1-17 Sebagai Konstruksi Teologi Yunus 1 - Anon Dwi Saputro (Predica Verbum: Jurnal Teologi dan Misi, 2022)
Yunus 1 is a book with a narrative genre. Several articles researched by the author, they agree that in Yunus 1 there is an irony figure of speech. However, from these articles, most of them only analyze and focus on studying the meaning of irony in Yunus 1 in depth. This study will discuss the figure of speech of irony in the Yunus 1 narrative as a theological construction in Yunus 1. The author uses a hermerneutic approach by paying attention to the narrative genre and using related literature. Exploration of meaning is also carried out by exegesis of the text of Yunus 1. This study aims to find the meaning of the ironic figure of speech in the narrative and to build the theology of Yunus 1 from that meaning. This article finds two antitheses, namely Yunus as the antithesis of the ideal prophet and the sailors as the antithesis of Yunus. The sailors met the true God through Jonah's disobedience. Another thing is in sync with Jonah's theology that God's grace applies to all nations including the sailors.